Improvement of Soil by Using Polymer Fiber Materials Underneath Square Footing (Journal of Engineering, 2013)
The change in project cost, or cost growth, occurs from many factors, some of which are related to soil problem conditions that may occurs during construction and/or during site investigation period. This paper described a new soil improvement method with a minimum cost solution by using polymer fiber materials having a length of (3 cm) in both directions and (2.5 mm) in thickness, distributed in uniform medium dense .sandy soil at different depths (B, 1.5B and 2B) below the footings. Three square footings has been used (5,7.5 and 10 cm) to carry the above investigation by using lever arm loading system design for such purposes. These fibers were distributed from depth of (0.1B) below the footing base down to the investigated depth. It was found that the initial vertical settlement of footing was highly affected in the early stage of loading due to complex Soil-Fiber Mixture (SFM) below the footing. The failure load value for proposed model in any case of loading increased compared with the un-reinforced soil by increasing the depth of improving below the footing. The Bearing Capacity Ratio (BCR) for soil-fiber mixture has been increased by ratio of (1.4 to 2.5), (1.7 to 4.9), and (1.8 to 8) for footings (5, 7.5, and 10 cm) respectively. The yield load-settlement for soil-fiber mixture system started at settlement of about 1.1% B while the yield load in un-reinforced soil started at smaller percentage which reflects the benefits of using such fiber materialfor improving soil behavior. Comparison between experimental and predicted (calculated) settlement below the footings showed the difference in ranges were within accepted limits for foundation settlements design